Examining the Impact of University Libraries in Facilitating Foreign Language Learning in Pakistan - Tania Ali Khan (IJoLIS, 2024)
Purpose: The field of language educatgion is thoughtfully evolving in the 21st century since liberaries aroung the world are offering substantial numbefr sof language learning resources to its users.